Of Hammers, Hurricanes, and History: Oscar Casares's Brownsville, Postracial Affect, and the Latina/o Studies Field-Imaginary. (4th April 2019) - Varon, Alberto
Abstract: This essay examines the material objects in Oscar Casares's short story collection Brownsville (2003), focusing on the short story "RG." The story's objects encode racial difference in the contemporary US. as affect—a feeling one knows but cannot prove—prefiguring the supposed postracial moment of the early twenty-first century. The objects serve as textual and material strategies that attempt to suture historical antagonism and that offer a model for the "objects" of study in Latina/o studies. Building on and against work in affect theory and new materialism, the essay argues for an affective mode of latinidad that links history and the present, contemporary Latina/o Studies with the past.